Factors Influencing the Intention to Purchase and Actual Purchase Behavior of Organic Food - Humaira, Assyifa; Hudrasyah, Herry (Journal of Business and Management, 2016)
Abstract.The organic market is widely considered as one of the biggest growing markets in food industry. The trends of healthy lifestyle also reflected in Indonesia. However, the number of consumer who purchases organic food in regular basis is reported to be low. To encourage consumption of organic foods, marketers must understand the consumers well to create better marketing strategy. Therefore, the objective of this study is to examine the factors that influence consumer intention and actual purchase behavior in the context of organic food. The proposed model of this study is using the modified Theory of Planned Behavior by Ajzen (1991) with added variables as determinants in organic food consumption. The research was conducted by distributing questionnaires to organic food consumers in Jakarta. Using the final data from 200 respondents, the data was analyzed by using Microsoft Excel, SPSS and assessed through Factor Analysis, One Way ANOVA, Multi Linear Regression, and Path Analysis. The result found that health consciousness, organic knowledge and trust have significant influence on attitude. As for the intention to purchase organic food, attitude has the strongest influence then followed by subjective norms and price. However, availability showed to have no significant influence on intention to purchase which demonstrated a different result from previous studies. Finally, actual purchase behavior found to greatly influenced by the intention to purchase itself.Keyword: Organic Food, Organic Consumers, Theory of Planned Behavior, Intention to Purchase, Actual Purchase Behavior